Qualitative comparison of the different lung ultrasound scores in children with bronchiolitis: a systematic review - Kogias, Christos; Prountzos, Spyridon; Alexopoulou, Efthymia; Douros, Konstantinos (International Journal of Contemporary Pediatrics, 2024)
Description and qualitative comparison of the lung ultrasound (LUS) scores used to assess patients aged 0 to 2 years with bronchiolitis. A systematic literature review was carried out to find out the LUS scores used to assess patients aged 0 to 2 years with bronchiolitis, using Medline, Scopus and ScienceDirect databases from their inception to January 2024. A total of 23 studies matching our eligibility criteria were analysed for the purposes of this review and 1878 patients with bronchiolitis were included. Different LUS scores were described and analysed. This review summarises the different scoring systems used in LUS in literature and the potential effects they may have had in diagnosing or monitoring bronchiolitis.